A scoping review exploring the uptake of the human papilloma virus vaccine amongst young women in Ireland - Shahzad, Varisha (International Journal Of Community Medicine And Public Health, 2025)
Human papillomavirus (HPV) is a sexually transmitted infection that can resolve spontaneously but may persist and lead to complications such as genital warts and cervical cancer. The National Cancer Registry Ireland (NCRI) reported an average of 264 new cases of invasive cervical cancer annually between 2015 and 2017, and 88 deaths per year between 2012 and 2014. Many of these could have been prevented through HPV vaccination. A scoping review was conducted to explore factors influencing HPV vaccine uptake among Irish women. The Arksey and O’Malley Framework guided the review process, and a preferred reporting items for systematic reviews and meta-analyses (PRISMA) flowchart was used to map the literature selection. The search covered studies published between 2008 and 2022. Nine studies met the inclusion criteria, employing both qualitative and quantitative methods. These studies explored various perspectives, with increasing interest in recent years—six studies were published in the last seven years. Seven of the nine studies focused on adult women. This scoping review highlights the current literature on HPV vaccination in Ireland, identifies gaps in understanding vaccine uptake, and offers suggestions for future research to address these gaps.